A compensation model developed to increase spectrum usage efficiency in the 4G era - Yuntsai Chou; Weimin Hu; Hsienming Lien (International Telecommunications Society (ITS), 2015)
Because fourth-generation (4G) mobile communications services are provided over refarmed and heterogeneous bands for the first time, a unified spectrum management regime fails to accommodate the spectral heterogeneity. In Taiwan, we still extend the 2G incumbents' usage right on the 900MHz and the 1800 MHz frequencies until 2015; meanwhile they have been refarmed for 4G uses since the late 2013. Likewise, the 2600 MHz frequencies are now considered for 4G auction in late this year (2015); nonetheless, they are currently assigned for wireless broadband access (WBA) services until 2020. This marks the telecommunications service providers' usage rights on the certain bandwidths are overlapping with each other, causing the unintended consequences of interference, hoarding, delayed deployment, and consequentially lack of spectrum usage efficiency.This paper is written to design an institution that mitigates the problem of unintended hoarding by the incumbents so that the spectrum can be swiftly switched to the supposedly more efficient uses. Facing the similar hoarding problem in the bandwidths of digital dividend, the US Federal Communication Commission (FCC) proposed incentive auction in hopes of compensating media broadcasters for their relinquishing the usage rights with the amount of bids paid by the winner. Even though the US Congress authorized the FCC to conduct incentive auctions in February, 2012, the FCC so far has not yet initiated once. This delay implies that incentive auction seems theoretically plausible but may not realistically feasible. Therefore, this study provides alternatives for efficient handover of spectrum usage rights.We hypothesized 4 scenarios for the WBA operators in hoarding the 2600 MHz frequencies. One is neither upgrade to 4G technologies and nor license renewal; the second is the upgrade allowed but no license renewal; the third is no upgrade but the license renewed; and fourth is both upgrade and renewal are allowed. We then employed econometric analysis to estimate the value of 2600 MHz frequencies under different usage restrictions. The value indicates the incumbent's willingness to forgo its usage right once compensated. Nevertheless, we observed that, even if with highest amount of compensation, the WBA incumbent may still opt to hoarding because it expects beyond-normal payoffs. Without the enforced mechanism rooted in incentive auction, the incumbent demonstrates opportunistic behavior to raise the payoffs in exchange its forgone usage of the bandwidths. We then devised an institution of the ad hoc clearing house guaranteed by the national regulatory authority (NRA). The NRA facilitates the transaction between the new owner and incumbent by acting as the third-party warrantee. Doing so could swiftly clear the used bandwidths and increase the efficiency of spectrum usage.
Keywords: 330; spectrum usage rights; refarming; incentive auction; spectrum value; evaluation methods